2009
DOI: 10.1002/ejlt.200800259
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, transesterification and process control in biodiesel production from Jatropha curcas

Abstract: Biodiesel has gained worldwide popularity as an alternative energy source due to its renewable, non-toxic, biodegradable and non-flammable properties. It also has low emission profiles and is environmentally beneficial. Biodiesel can be used either in pure form or blended with conventional petrodiesel in automobiles without any major engine modifications. Various non-edible and edible oils can be used for the preparation of biodiesel. With no competition with food uses, the use of non-edible oils as alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 89 publications
1
31
1
6
Order By: Relevance
“…Biodiesel (B) is a fuel produced from plant oils in the reaction of (trans)esterification, where glycerides and free fatty acids (F) interact with an alcohol (typically methanol, MeOH) [1][2][3][4][5][6]. Use of alkaline catalysts (KOH, NaOH, methoxide, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel (B) is a fuel produced from plant oils in the reaction of (trans)esterification, where glycerides and free fatty acids (F) interact with an alcohol (typically methanol, MeOH) [1][2][3][4][5][6]. Use of alkaline catalysts (KOH, NaOH, methoxide, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanical effect caused by ultrasound may also be the agitation of the solvent used for extraction, thus increasing the contact surface area between the solvent and targeted compounds by permitting greater penetration of solvent into the sample matrix. The ultrasonic-assisted extraction (UAE) also required shorter extraction times and reduced solvent consumption (Li et al, 2004;Mason et al, 2011;Nazir et al, 2009;Zhang et al, 2008). Whereas Hromadkova et al (1999) reported that, ultrasound-assisted extraction can be carried out at a lower temperature which can avoid thermal damage to the extracts and minimize the loss of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, methods have to be applied to reduce the oil viscosity and modify the properties of vegetable oils, e.g., blending, microemulsification, pyrolysis, and transesterification [14]. Among these procedures, transesterification is preferentially used for acceptable efficiency and lower production cost of catalyst [15]. Transesterification is a chemical three-step reaction between triglyceride and alcohol in the presence of an alkali, acidic, or enzymatic catalyst to produce fatty acid methyl esters (FAMEs; biodiesel) [12].…”
Section: Introductionmentioning
confidence: 99%